Ionic conductivity enhancement of PVA: carboxymethyl cellulose poly-blend electrolyte films through the doping of NaI salt - Cyriac, Vipin; Noor, I. M.; Mishra, Kuldeep; Chavan, Chetan; Bhajantri, Rajashekhar F.; Masti, Saraswati P. (Springer, 2022)
In this paper, we report the effect of doping sodium iodide (NaI) salt into a polymer blend matrix of sodium carboxymethyl cellulose (NaCMC) and poly(vinyl alcohol) (PVA). Solution casting approach was used to prepare solid polymer electrolyte (SPE) films. The films were characterized by Fourier-transform infrared spectroscopy (FTIR), X-Ray diffraction (XRD), electrical impedance spectroscopy, thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC). XRD showed that NaI incorporation decreased the crystallinity of NaCMC/PVA-based SPE. FTIR technique confirmed the complexation of salt with polymer matrix due to the formation of the coordination bond between Na+ and –OH group and hydrogen bond between I− and –CH group. The sample with 30 wt% NaI showed the highest conductivity of 2.52 × 10–3 S cm−1, strongly influenced by the highest charge concentration (n), not its mobility (μ). DSC analysis revealed an increase in glass transition temperature (Tg) with increasing salt content. TGA studies showed a decrease in thermal stability with salt inclusion. The transference number was found to be 0.99 for the highest conducting sample showing the primary charge carriers are ions. The highest conducting sample exhibited a mechanical strength of 15.42 MPa at room temperature, and it has been used to fabricate a battery to evaluate its suitability in energy storage devices.